Modified clay for roadbed as well as preparation method and application of modified clay

By using the modified clay curlers prepared by alpine, phosphoric acid, and industrial waste residue-branfallal residue, the engineering problems existing in low-liquid-limited soil in the roadfilling are solved, and the mechanical properties of the soil are significantly improved, realizing environmental protection and efficiency The basis solidification effect.

CN119351119AInactive Publication Date: 2025-01-24UNIV OF JINAN +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411480383.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, low liquid limit soil is easily caused by uneven settlement, cracking, sliding and other engineering problems when used in roadbed filling, and traditional curing agents consume a large amount of energy and produce harmful emissions during the production process.

Method used

The use of kaolin, phosphate and industrial waste residue-branfamal residue is used as raw materials. The mix of mixing with mechanical mixing and mixing water is used to prepare a modified clay curing agent to improve the mechanical properties of low liquid limited clay.

Benefits of technology

It significantly improves the unconfined compressive strength, shear strength, shrinkage resistance and expansion resistance of low liquid limit clay, and is environmentally friendly, reducing energy consumption and harmful emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351119A_ABST
    Figure CN119351119A_ABST
Patent Text Reader

Abstract

The invention discloses modified clay for a roadbed as well as a preparation method and application of the modified clay, and belongs to the technical field of soil solidification. The modified clay for the roadbed consists of the following components in parts by weight: 100 parts of low liquid limit clay; 30-70 parts by weight of a curing agent; 18.5 to 20.3 parts by weight of water; the curing agent is prepared from a phosphoric acid aqueous solution, metakaolin and furfural residues in a mass ratio of 1: 2: (2-3); the concentration of the phosphoric acid aqueous solution is 85.54 wt%; the total moisture content of the modified clay for the roadbed is 21 parts by weight. The mixture of the phosphoric acid aqueous solution, the metakaolin and the furfural residues is selected as the curing agent, so that the unconfined strength, the shear strength, the shrinkage resistance and the expansion resistance of the low-liquid-limit clay can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soil solidification, in particular to modified clay for roadbed and a preparation method and application thereof. Background Art

[0002] If low liquid limit soil is used for roadbed filling, it is easy to cause engineering problems such as uneven settlement, cracking, and sliding, so it cannot be directly used for roadbed filling. At present, low liquid limit soil for engineering is mainly improved by traditional curing agents such as cement, lime, and fly ash. These curing agents undergo a series of physical and chemical reactions with soil particles, improving the engineering properties of the soil by changing the particle composition and mineral composition of the soil.

[0003] Traditional curing agents also have some negative effects. For example, the strong alkaline environment formed by inorganic curing agents will pollute the surrounding soil and groundwater. Most modified clays are brittle soils, which are not conducive to the stability of the roadbed under traffic loads. In addition, the production of cement and lime not only consumes a large amount of limestone, clay, electricity, and heat energy, but also emits harmful substances that affect air quality, such as CO 2 、SO 2 , dust, etc.

[0004] Geopolymers are an important inorganic polymer material that has attracted increasing attention due to their low density, excellent thermodynamic and mechanical properties, outstanding fire resistance, good chemical stability, and impermeability. Geopolymers can be used in high-temperature refractory ceramics, refractory thermal insulation coatings and adhesives, new binders for refractory building materials, radioactive waste sequestration, and cement-based components in cement and concrete. The raw materials of geopolymers are usually natural aluminosilicate minerals such as high-alumina cement, volcanic ash, or some industrial by-products such as fly ash, slag, etc. Compared with traditional Portland cement, which consumes a lot of energy and produces a lot of carbon dioxide emissions in its production, geopolymers are generally considered to be green materials, with carbon dioxide emissions reduced by about 80%. Therefore, geopolymers offer a considerable opportunity as the most promising soil stabilizer.

[0005] Common geopolymers are made from fly ash, slag and kaolin as the main raw materials. 2 SiO 3 Alkali aluminosilicate (AAS) geopolymers are prepared by activation with alkali under alkaline conditions. Phosphate-activated aluminosilicate materials are a relatively new topic compared to AAS geopolymers, which involves the preparation of silicoaluminophosphate (SAP) geopolymers by activation with phosphate or phosphoric acid. SAP geopolymers have excellent properties such as high mechanical strength, high temperature resistance, low dielectric constant and dielectric loss, and have broad potential application prospects in building materials, high temperature refractory materials, high temperature packaging or encapsulation materials, etc.

[0006] Therefore, as people pay more and more attention to environmental issues, it is particularly important to design a low liquid limit curing agent that is both economical and environmentally friendly. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a modified clay for roadbed and a preparation method and application thereof; the present invention adopts metakaolin (MK), phosphoric acid and industrial waste residue-furfural residue as raw materials, and the prepared soil solidification technology is used to improve the mechanical properties of low liquid limit clay.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0009] In one aspect, the present invention provides a modified clay for roadbed, which is composed of the following components by weight: 100 parts by weight of low liquid limit clay; 30-70 parts by weight of curing agent; 18.5-20.3 parts by weight of water;

[0010] The curing agent is a phosphoric acid aqueous solution, metakaolin and furfural residue in a mass ratio of 1:2:2-3;

[0011] The concentration of the phosphoric acid aqueous solution is 85.54wt%;

[0012] The total moisture content of the modified clay for roadbed is 21 parts by weight;

[0013] The furfural residue is prepared by the following method: the purchased furfural residue is crushed, passed through a 0.5 mm sieve, and then dried in an oven to constant weight, and then sieved through a sieve with an aperture of 0.5 mm to obtain the furfural residue.

[0014] The low liquid limit clay of the present invention has a soil particle size (≤0.075 mm) of ≥50%, a liquid limit wl≤50%, and a plasticity index Ip>7.

[0015] On the other hand, the present invention also provides a method for preparing the modified clay for roadbed, which comprises firstly mechanically stirring and mixing the low liquid limit clay and the curing agent evenly, then adding water and stirring evenly.

[0016] On the other hand, the present invention also provides an application of the modified clay for roadbed, which can be used as different grades of highway base or subbase according to the unconfined compressive strength of the prepared modified clay.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The industrial waste residue-furfural residue selected by the present invention contains a large amount of lignin and cellulose. Lignin and cellulose play a major role in the solidification of low liquid limit clay by industrial waste residue-furfural residue. On the one hand, lignin produces a gelling substance when mixed with water. The filling and cementation of lignin and the thinning of the double electric layer in the modified low liquid limit clay achieve the purpose of enhancing the strength of the soil. Cellulose provides additional interlocking and bridging effects, and the fiber's adsorption of fine particles and water achieves the purpose of solidifying the low liquid limit soil. On the other hand, phosphoric acid forms a geopolymer with metakaolin, [PO 4 ] 3- The tetrahedral unit reacts with the Si-O layer to form an amorphous (-Si-O-P-O-) structure and reacts with the leached aluminum to form a crystalline AlPO 4 The final product of the phosphate-based geopolymer is a crystalline AlPO 4 Geopolymer composite materials composed of an amorphous (Si-O-P-O) structure can greatly enhance the strength of the soil. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the unconfined compressive strength graph of Comparative Examples 6-8 (5%PA, 10%PA, 15%PA), Comparative Examples 3-5 (15%FR+5%PA, 15%FR+10%PA, 15%FR+15%PA), Comparative Examples 9-11 (10%MK+5%PA, 20%MK+10%PA, 30%MK+15%PA) and Examples 1-3 (15%FR+10%MK+5%PA, 15%FR+20%MK+10%PA, 15%FR+30%MK+15%PA);

[0020] Figure 2 The cohesion and internal friction angle diagrams of Comparative Example 1 (blank), Comparative Example 2 (15% FR), Example 1 (15% FR + 10% MK + 5% P), Example 2 (15% FR + 20% MK + 10% PA), and Example 3 (15% FR + 30% MK + 15% PA);

[0021] Figure 3 The shrinkage diagrams are for Comparative Example 1 (blank), Comparative Example 2 (15% FR), Example 1 (15% FR+10% MK+5% P), Example 2 (15% FR+20% MK+10% PA), and Example 3 (15% FR+30% MK+15% PA); wherein, es: linear shrinkage; ev: volume shrinkage;

[0022] Figure 4The no-load expansion rate diagrams are for Comparative Example 1 (blank), Comparative Example 2 (15% FR), Example 1 (15% FR+10% MK+5% P), Example 2 (15% FR+20% MK+10% PA), and Example 3 (15% FR+30% MK+15% PA); DETAILED DESCRIPTION

[0023] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0024] In the present invention, the materials and reagents used are all commercially available unless otherwise specified. The concentration of the phosphoric acid aqueous solution is 85.54 wt %. Metakaolin: purchased from Gongyi Chenyi Refractory Abrasive Co., Ltd. Metakaolin composition: SiO 2 55%,Al 2 O 3 44%, TiO 2 0.2%, CaO 0.2%, MgO 0.05%, K 2 O 0.5%, Na 2 O 0.05%; furfural residue: purchased from Binzhou Huitong Bioenergy Co., Ltd.; the low liquid limit clay used in the present invention: the soil particles with a particle size (≤0.075mm) are 94.9%, the natural water content w is 9.2%, the liquid limit wl is 39.5%, the plasticity index Ip is 12.6, and the maximum dry density is 1.63g / cm 3 , the optimal moisture content is 21.0%.

[0025] The present invention provides modified clay for roadbed and a preparation method and application thereof, and specific embodiments are as follows.

[0026] Example 1

[0027] A modified clay for roadbed consists of the following components in parts by weight: 100 parts by weight of low liquid limit clay; 30 parts by weight of a curing agent; and 21 parts by weight of water. The curing agent comprises 5 parts by weight of a phosphoric acid aqueous solution, 10 parts by weight of metakaolin, and 15 parts by weight of furfural residue.

[0028] The furfural residue is prepared by the following method: the purchased furfural residue is first crushed and passed through a 0.5 mm sieve, at which the moisture content is 42.6%, and then dried in an oven at a temperature of 105° C. for 24 hours, and then the dried furfural residue is sieved using a sieve with an aperture of 0.5 mm.

[0029] The method for preparing the modified clay for roadbed is: firstly mechanically stir and mix the low liquid limit clay and the curing agent evenly, then add water and stir evenly.

[0030] Embodiment 2-5

[0031] The substances and amounts of modified clay for roadbed in Examples 2-5 are shown in Table 1, and the other conditions are the same as in Example 1.

[0032] Table 1

[0033]

[0034] In the early stage, the inventors studied that phosphoric acid mixed with furfural residue as a curing agent has a certain curing effect on low liquid limit clay, which is used as a comparison as follows.

[0035] Comparative Example 1

[0036] In this comparative example, 100 parts by weight of low liquid limit clay and 21 parts by weight of water were used, and the rest was the same as in Example 1.

[0037] Comparative Example 2

[0038] In this comparative example, 100 parts by weight of low liquid limit clay, 15 parts by weight of furfural residue, and 21 parts by weight of water are used, and the rest is the same as in Example 1.

[0039] Comparative Example 3

[0040] In this comparative example, only phosphoric acid aqueous solution and furfural residue are used as curing agent, wherein the phosphoric acid aqueous solution comprises 5 parts by weight and the furfural residue comprises 15 parts by weight, and the other conditions are the same as those in Example 1.

[0041] Comparative Example 4

[0042] In this comparative example, only phosphoric acid aqueous solution and furfural residue are used as curing agents. The curing agent contains 10 parts by weight of phosphoric acid aqueous solution and 15 parts by weight of furfural residue. The other conditions are the same as those in Example 1.

[0043] Comparative Example 5

[0044] In this comparative example, only phosphoric acid aqueous solution and furfural residue are used as curing agent, wherein the phosphoric acid aqueous solution comprises 15 parts by weight, and the furfural residue comprises 15 parts by weight. The other conditions are the same as those in Example 1.

[0045] The inventor mixed the curing agent and the low liquid limit clay mechanically by mixing them evenly according to the dosage of each substance in different embodiments and comparative examples, then added water and mixed them evenly again; then sealed them with plastic wrap, stored them for 12 hours, and used a compression molding and demolding integrated machine to make a sample with a length of 100 mm and a diameter of 50 mm, and then carried out unconfined compressive strength, direct shear, shrinkage and expansion test samples, and tested them. The specific process is as follows.

[0046] 1. Unconfined compressive strength test

[0047] The test process was carried out using an unconfined compression apparatus model YAW-300D / 10D.

[0048] How to do it:

[0049] (1) Sample preparation: The material that has been simmered for 12 hours is molded into a sample with a length of 100 mm and a diameter of 50 mm using a die-pressing and demolding integrated machine, and the height is measured and the weight is weighed;

[0050] (2) Curing: All samples were cured in a standard curing box for 7 days at a temperature of 20 ± 2 °C and a relative humidity of 95 ± 3%.

[0051] (3) Test: The unconfined compressive strength machine parameters were adjusted to a loading speed of 1 mm / min. The procedure was based on the "Unconfined Compressive Strength Test for Inorganic Bonds in Highway Engineering" [JTG E51-2009]. The test was conducted after the surface of the specimen was scraped flat, the height was measured, and the mass was weighed. The results are shown in Tables 2-3 and Figure 1 , the furfural residue dosage in the figure is the weight ratio of furfural residue to low liquid limit clay.

[0052] 2. Shear test

[0053] In the direct shear test, the solidification quick shear test is adopted and carried out in strict accordance with the requirements of the test regulations. The test process is carried out using a direct shear apparatus with the model ZJ Quadruplex Strain Controllde.

[0054] How to do it:

[0055] (1) Align the upper and lower boxes of the shear container and insert the fixing pins, and place the permeable stone and filter paper into the lower box.

[0056] (2) Align the blade of the ring knife and the sample (specimen with a length of 100 mm and a diameter of 50 mm) upwards to the opening of the shear box, place filter paper and permeable stone on the sample, and carefully push the sample into the shear box for testing.

[0057] (3) The shear displacement and shear stress of clay samples modified with furfural residues at different dosages were obtained, and the shear strength of the modified clay was calculated. The shear strength of the specimens was calculated by the shear strength indexes cohesion (c) and internal friction angle (φ). Four horizontal loads of 100, 200, 300, and 400 kN were set for vertical loading. The shear rate was about 0.8 mm / min, and the shearing of the specimens was controlled to be completed within 3-5 minutes. The results are shown in Tables 2-3 and Figure 2 , the furfural residue dosage in the figure is the weight ratio of furfural residue to low liquid limit clay.

[0058] 3. Shrinkage test

[0059] The test was carried out using a SS-1 shrinkage instrument.

[0060] How to do it:

[0061] (1) Push the prepared sample (length 100 mm, diameter 50 mm) out of the ring cutter and place it on the perforated plate.

[0062] (2) Weigh the mass of the sample and the porous plate, install the dial gauge and record the initial reading. Record the percentage reading every 1-4 hours, and then weigh the weight of the entire device and the sample. After 2 days, record the dial gauge reading every 6-24 hours and weigh the weight of the entire device and the sample until the two percentage readings are consistent. The results are shown in Figure 3 and Table 2, in which the furfural residue dosage is the weight ratio of the furfural residue to the low liquid limit clay.

[0063] 4. Expansion test

[0064] The test process was carried out using a WZ-2 dilatometer.

[0065] How to do it:

[0066] (1) Place a wet permeable stone in the base and screw the blunt end of the ring cutter onto the base so that the surface of the sample contacts the top surface of the permeable stone.

[0067] (2) After the specimen (100 mm in length and 50 mm in diameter) is in place, place the piston plate with holes on the top of the specimen, align it with the center of the piston, install the dial indicator and record the dial indicator reading.

[0068] (3) Pour pure water into the basin and keep the water level in the basin roughly the same as the bottom of the sample.

[0069] (4) Record the time when water injection begins, and record the dial gauge readings at 5, 10, 20, 30 minutes, 1, 2, 3, 24 hours, and every 24 hours thereafter until the sample stops expanding. Figure 4 As shown in Table 2-3, the furfural residue dosage is the weight ratio of the furfural residue to the low liquid limit clay.

[0070] Table 2

[0071]

[0072]

[0073] As shown in Table 2, the unconfined compressive strength value of the curing agent modified clay of the present invention increases with the increase of the curing agent dosage. It is worth noting that when the curing agent dosage is 60% of the low liquid limit clay, the unconfined compressive strength value is the largest, reaching 3965.68 kPa after curing for 7 days, exceeding the modified clay prepared by using only 15% furfural slag as a curing agent (Comparative Example 2), 3089.54 kPa higher than the unconfined compressive strength value (876.14 kPa) of the modified clay prepared by using only 15% furfural slag as a curing agent (Comparative Example 2), and 3433.21 kPa higher than the unconfined compressive strength value (343.67 kPa) of natural clay. The unconfined compressive strength value of the cured soil has far exceeded the 7d-age unconfined compressive strength standard (maximum strength 1.1 MPa) of the lime fly ash stabilized material.

[0074] As the amount of curing agent increases, the cohesion and internal friction angle of the furfural residue modified clay gradually increase. When the furfural residue content is 60% of the low liquid limit clay, the cohesion and internal friction angle of the clay are the highest, which are 213.7% and 93.7% higher than the modified clay prepared by using only 15% furfural residue as a curing agent (Comparative Example 2), and 989.8% and 154.8% higher than natural clay, respectively, and the shear strength is excellently improved.

[0075] As the amount of furfural residue increases, the linear shrinkage (es) and volume shrinkage (ev) gradually decrease. When the amount of furfural residue reaches 15% of the low liquid limit clay and reaches the lowest value, the linear shrinkage (es) and volume shrinkage (ev) are reduced by 87.5% and 146.2% respectively compared with Comparative Example 1, and by 56.3% and 54.9% respectively compared with Comparative Example 2, and the anti-shrinkage performance is significantly improved.

[0076] The no-load expansion rate of comparative example 1 is 5.20%. When the curing agent dosage increases from 30% to 60% of the low liquid limit clay, the expansion rate of the clay decreases significantly, by 136.4%. When the curing agent dosage is 60% of the low liquid limit clay, the minimum expansion rate is 2.20%. It can be seen that the curing agent has an improving effect on the expansion rate of the low liquid limit clay.

[0077] The performance of the modified clay prepared by using a simple phosphoric acid aqueous solution or a phosphoric acid aqueous solution mixed with furfural residue as a curing agent is lower than that of the embodiment of the present invention.

[0078] To further illustrate the beneficial effects of the present invention, the inventors conducted further research on the composition and dosage ratio of the curing agent, as follows.

[0079] Comparative Example 6

[0080] In this comparative example, only phosphoric acid aqueous solution is used as the curing agent, and the phosphoric acid aqueous solution in the curing agent is 5 parts by weight, and the other conditions are the same as those in Example 1.

[0081] Comparative Example 7

[0082] In this comparative example, only phosphoric acid aqueous solution is used as the curing agent, and the phosphoric acid aqueous solution in the curing agent is 10 parts by weight. The other conditions are the same as those in Example 2.

[0083] Comparative Example 8

[0084] In this comparative example, only phosphoric acid aqueous solution is used as the curing agent, and the phosphoric acid aqueous solution in the curing agent is 15 parts by weight, and the other conditions are the same as those in Example 3.

[0085] Comparative Example 9

[0086] In this comparative example, only phosphoric acid aqueous solution and metakaolin are used as curing agents. The curing agent contains 5 parts by weight of phosphoric acid aqueous solution and 10 parts by weight of metakaolin. Other conditions are the same as those in Example 1.

[0087] Comparative Example 10

[0088] In this comparative example, only phosphoric acid aqueous solution and metakaolin are used as curing agents. The curing agent contains 10 parts by weight of phosphoric acid aqueous solution and 20 parts by weight of metakaolin. Other conditions are the same as those in Example 2.

[0089] Comparative Example 11

[0090] In this comparative example, only phosphoric acid aqueous solution and metakaolin are used as curing agents. The curing agent contains 15 parts by weight of phosphoric acid aqueous solution and 30 parts by weight of metakaolin. Other conditions are the same as those in Example 3.

[0091] Comparative Example 12

[0092] The mass ratio of phosphoric acid aqueous solution: metakaolin: furfural residue in the curing agent is 1:1:1; the other conditions are the same as those in Example 3.

[0093] Comparative Example 13

[0094] The mass ratio of phosphoric acid aqueous solution: metakaolin: furfural residue in the curing agent is 2:1:1; the other conditions are the same as those in Example 3.

[0095] Comparative Example 14

[0096] The mass ratio of phosphoric acid aqueous solution: metakaolin: furfural residue in the curing agent is 1:1:2; the other conditions are the same as those in Example 3.

[0097] Comparative Example 15

[0098] The mass ratio of phosphoric acid aqueous solution: metakaolin: furfural residue in the curing agent is 2:2:1; the other conditions are the same as those in Example 3.

[0099] Comparative Example 16

[0100] The mass ratio of phosphoric acid aqueous solution: metakaolin: furfural residue in the curing agent is 1:3:1; the other conditions are the same as those in Example 3.

[0101] Comparative Example 17

[0102] The mass ratio of phosphoric acid aqueous solution: metakaolin: furfural residue in the curing agent is 1:2:4; the other conditions are the same as those in Example 3.

[0103] Comparative Example 18

[0104] In this comparative example, the amount of curing agent used is 20 parts, and the mass ratio of phosphoric acid aqueous solution: metakaolin: furfural residue in the curing agent is 1:2:1; the other conditions are the same as those in Example 3.

[0105] Comparative Example 19

[0106] In this comparative example, the amount of curing agent used is 80 parts, and the mass ratio of phosphoric acid aqueous solution: metakaolin: furfural residue in the curing agent is 1:2:1; the other conditions are the same as those in Example 3.

[0107] The inventors mixed the curing agent and low liquid limit clay in the above-mentioned different comparative examples by unloading and stirring, and then added water to reach a moisture content of 21%, and mixed them again; then sealed with plastic wrap, stored for 12 hours, and used a compression mold and demolding integrated machine to make a sample with a length of 100 mm and a diameter of 50 mm, and then carried out an unconfined compressive strength test. The results are shown in Table 3.

[0108] Table 3

[0109]

[0110]

[0111] It can be seen from Table 2-3 that when the curing agent is only an aqueous phosphoric acid solution (Comparative Examples 6-8) or the curing agent is a mixture of an aqueous phosphoric acid solution and kaolin (Comparative Examples 9-11), the unconfined compressive strength of the prepared modified clay is greatly reduced compared with Example 3; and the unconfined compressive strength of the prepared modified clay by the compounding of aqueous phosphoric acid solution, kaolin and furfural residue is significantly different depending on the proportion of the three, and is much lower than the unconfined compressive strength of Example 3.

[0112] When the amount of curing agent is less (Comparative Example 18) or more (Comparative Example 19), the unconfined compressive strength is also lower than that of the embodiment.

[0113] The present invention also provides an application of the modified clay for roadbed, which can be used as highway base or subbase of different grades according to the unconfined compressive strength of the prepared modified clay. The reference is the provisions of 4.2.6 of "Technical Specifications for Construction of Highway Pavement Base" (JTG / T F20-2015).

[0114] In summary, the present invention can significantly improve the unconfined strength, shear strength, shrinkage resistance and expansion resistance of low liquid limit clay by selecting a mixture of phosphoric acid aqueous solution, metakaolin and furfural residue as a curing agent.

[0115] The above is a preferred embodiment of the present invention. For ordinary technicians in this technical field, making several improvements and modifications without departing from the principles of the present invention should also be regarded as within the protection scope of the present invention.

Claims

1. A modified clay for roadbed, characterized in that: The modified clay for roadbed is composed of the following components by weight: 100 parts by weight of low liquid limit clay; 30-70 parts by weight of curing agent; 18.5-20.3 parts by weight of water; The curing agent is a phosphoric acid aqueous solution, metakaolin and furfural residue in a mass ratio of 1:2:2-3; The concentration of the phosphoric acid aqueous solution is 85.54wt%; The total moisture content of the modified clay for roadbed is 21 parts by weight; The furfural residue is prepared by the following method: the purchased furfural residue is crushed, passed through a 0.5 mm sieve, and then dried in an oven to constant weight, and then sieved through a sieve with an aperture of 0.5 mm to obtain the furfural residue.

2. The method for preparing modified clay for roadbed according to claim 1, characterized in that: First, mechanically stir the low liquid limit clay and curing agent to mix evenly, then add water and stir again to mix evenly.

3. The use of modified clay for roadbed according to claim 1, characterized in that: The unconfined compressive strength of the prepared roadbed modified clay is used as the subbase or base of the highway.